2017
DOI: 10.1186/s12895-017-0066-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effects of skin microneedling as adjuvant therapy for facial melasma: a pilot study

Abstract: BackgroundMelasma is a common chronic and relapsing acquired dyschromia. Skin microneedling was reported resulting sustained long-term improvement of recalcitrant melasma, however, the exact mechanism that promotes this skin lightening is not known. This study aimed to investigate clinical and histologic alterations promoted by skin microneedling in facial melasma.MethodsOpen pilot trial including six women with facial refractory melasma submitted to two sessions of microneedling (1.5 mm) each 30 days followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 43 publications
2
34
0
8
Order By: Relevance
“…In an open trial, Lima et al reported a significant reduction of MASI score from 37.1 to 11.0 (70% mean decrease in MASI) after two sessions of microneedling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an open trial, Lima et al reported a significant reduction of MASI score from 37.1 to 11.0 (70% mean decrease in MASI) after two sessions of microneedling.…”
Section: Discussionmentioning
confidence: 99%
“…This produces small holes known as micro‐conduits, with minimal damage to the epidermis, allowing migration of epithelial and endothelial cells. The procedure has been shown to promote growth factor release and thus stimulate fibroblast proliferation, while also enhancing collagen and elastin production in the papillary layer of the epidermis, inducing beneficial wound healing with a few side‐effects …”
Section: Introductionmentioning
confidence: 99%
“…A similar penetration of pharmaceuticals was confirmed also with the use of dermaroller just before the substance application (Šuca et al, ). Moreover, the increase in transepidermal drug delivery is observed for at least 72 hr after the procedure (Lima, Lima, Paixão, & Miot, ). The microtraumatization creates micropores, which results in increased transdermal water loss (Šuca et al, ), however, the result of the study has demonstrated that prompt recovery of skin barrier function is achieved within several hours from device usage (Shah, Shah, Solanki, & Raval, ).…”
Section: Most Commonly Used Devicesmentioning
confidence: 99%
“…20 The long-term improvement of recalcitrant melasma after micro needle treatment has been reported in case series studies, however, the exact mechanism that promotes skin clearance is unknown. 18,19 In a small study conducted in patients from the northeast of Brazil by Lima and colleagues, after the performance of 2sessions with micro needles subjective improvement of the skin smoothness and greater luminosity in patients with recalcitrant melasma was observed. A decrease of 70% in the MASI, 13% increase in luminosity and 55% decrease in the melasma quality of life scale was evidenced.…”
Section: Use In Melasma and Melanogenesismentioning
confidence: 99%
“…The micro needles began to be used for the treatment of acne scars and it was observed that in patients with concomitant melasma, there was an improvement in the decrease of the pigment in the skin. 18,19 In this way, it was begun to be explored as a means of transdermal drug administration in a population with Fitzpatrick III-IV-V phototype, for the treatment of hyper pigmentation disorders. 20 The long-term improvement of recalcitrant melasma after micro needle treatment has been reported in case series studies, however, the exact mechanism that promotes skin clearance is unknown.…”
Section: Use In Melasma and Melanogenesismentioning
confidence: 99%